Images and monuments of near eastern dynasts, 100 BC-AD 100 - Kropp, Andreas J. M. 1977- (Oxford studies in ancient culture and representation., 2013)
This book is an archaeological and art-historical study of the images and monuments of Roman 'client' kings in the Near East from the Taurus to Edom (modern South East Turkey, Syria, Lebanon, Israel, Palestine, and Jordan) in the important transitional period between the downfall of the Seleucid empire and Rome's establishment of provincial administration across the entire region. In this volume, Kropp treats royal portraits, tombs, palaces, coins, and temples as historical documents and aims at uncovering royal identities and ideological aspirations. In particular, he focuses on the six major players: the Kommagenian, Emesan, Ituraean, Nabataean, Hasmonaean, and Herodian dynasties.